Students' and Teachers' Perceptions of Undergraduate Conducting Curricula: A Review of Literature. (October 2019) - Noon, Christian M.
Conducting courses are a common component of undergraduate instrumental music education programs. The experiences students have in those courses vary across and sometimes within institutions. This variation is due to many factors including choice of instructional materials and sequences, as well as whether textbooks or other instructional approaches (e.g., Laban movement theory) are used and how classes are designed for students to practice and refine their conducting. In this review, I summarized and synthesized literature related to the structure and content of undergraduate conducting curricula, as well as students' and teachers' perceptions of those curricula. I also made suggestions for teaching practice and for further research, and proposed a shift in the discourse on undergraduate conducting curricula toward authentic context, pedagogy-rich coursework aimed at preparing students to successfully adopt the conductor-educator role in their future careers.